Move <math><mstyle displaystyle="true"><msup><mrow><mi>x</mi></mrow><mrow><mo>-</mo><mn>4</mn></mrow></msup></mstyle></math> .

Use the power rule <math><mstyle displaystyle="true"><msup><mrow><mi>a</mi></mrow><mrow><mi>m</mi></mrow></msup><msup><mrow><mi>a</mi></mrow><mrow><mi>n</mi></mrow></msup><mo>=</mo><msup><mrow><mi>a</mi></mrow><mrow><mi>m</mi><mo>+</mo><mi>n</mi></mrow></msup></mstyle></math> to combine exponents.

Add <math><mstyle displaystyle="true"><mo>-</mo><mn>4</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math> .

Move <math><mstyle displaystyle="true"><msup><mrow><mi>x</mi></mrow><mrow><mo>-</mo><mn>3</mn></mrow></msup></mstyle></math> .

Use the power rule <math><mstyle displaystyle="true"><msup><mrow><mi>a</mi></mrow><mrow><mi>m</mi></mrow></msup><msup><mrow><mi>a</mi></mrow><mrow><mi>n</mi></mrow></msup><mo>=</mo><msup><mrow><mi>a</mi></mrow><mrow><mi>m</mi><mo>+</mo><mi>n</mi></mrow></msup></mstyle></math> to combine exponents.

Add <math><mstyle displaystyle="true"><mo>-</mo><mn>3</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Move <math><mstyle displaystyle="true"><msup><mrow><mi>y</mi></mrow><mrow><mn>4</mn></mrow></msup></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><msup><mrow><mi>y</mi></mrow><mrow><mn>4</mn></mrow></msup></mstyle></math> by <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> .

Raise <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> to the power of <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Use the power rule <math><mstyle displaystyle="true"><msup><mrow><mi>a</mi></mrow><mrow><mi>m</mi></mrow></msup><msup><mrow><mi>a</mi></mrow><mrow><mi>n</mi></mrow></msup><mo>=</mo><msup><mrow><mi>a</mi></mrow><mrow><mi>m</mi><mo>+</mo><mi>n</mi></mrow></msup></mstyle></math> to combine exponents.

Add <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Rewrite using the commutative property of multiplication.

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>5</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Rewrite the expression using the negative exponent rule <math><mstyle displaystyle="true"><msup><mrow><mi>b</mi></mrow><mrow><mo>-</mo><mi>n</mi></mrow></msup><mo>=</mo><mfrac><mrow><mn>1</mn></mrow><mrow><msup><mrow><mi>b</mi></mrow><mrow><mi>n</mi></mrow></msup></mrow></mfrac></mstyle></math> .

Combine <math><mstyle displaystyle="true"><mo>-</mo><mn>10</mn></mstyle></math> and <math><mstyle displaystyle="true"><mfrac><mrow><mn>1</mn></mrow><mrow><mi>x</mi></mrow></mfrac></mstyle></math> .

Move the negative in front of the fraction.

Combine <math><mstyle displaystyle="true"><msup><mrow><mi>y</mi></mrow><mrow><mn>5</mn></mrow></msup></mstyle></math> and <math><mstyle displaystyle="true"><mfrac><mrow><mn>10</mn></mrow><mrow><mi>x</mi></mrow></mfrac></mstyle></math> .

Move <math><mstyle displaystyle="true"><mn>10</mn></mstyle></math> to the left of <math><mstyle displaystyle="true"><msup><mrow><mi>y</mi></mrow><mrow><mn>5</mn></mrow></msup></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>6</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> .

Combine <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math> and <math><mstyle displaystyle="true"><mfrac><mrow><mn>10</mn><msup><mrow><mi>y</mi></mrow><mrow><mn>5</mn></mrow></msup></mrow><mrow><mi>x</mi></mrow></mfrac></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mn>10</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math> .

Do you know how to Simplify (-5x^6)(2x^-4y)(-6x^-3y^4)? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.